Tubercular breast abscess presenting as breast mastitis: a rare case report - Patel, Nikunj Kamleshbhai; Agrawal, Bhavdeep P. (International Surgery Journal, 2025)
Tuberculous breast abscess is an uncommon manifestation of extrapulmonary tuberculosis (TB), often misdiagnosed due to its rarity and resemblance to pyogenic breast abscesses or malignancy. We report the case of a 37-year-old female who presented with unilateral left-sided breast swelling, pain, and fever. Ultrasound findings suggested a breast abscess, and the patient underwent incision and drainage. Pus was sent for culture and CBNAAT testing, which later confirmed a tubercular etiology. The patient was subsequently treated with a 6-month course of antitubercular therapy, with complete resolution of symptoms on follow-up.